2013
DOI: 10.1007/s12013-013-9708-3
|View full text |Cite
|
Sign up to set email alerts
|

MiR-335, an Adipogenesis-Related MicroRNA, is Involved in Adipose Tissue Inflammation

Abstract: During the development of obesity, adipose tissue releases a host of different adipokines and inflammatory cytokines, such as leptin, resistin, tumor necrosis factor α (TNF-α), Interleukin-6 (IL-6), and adiponectin, which mediate insulin resistance. Recently, some microRNAs (miRNAs) regulated by adiponectin were identified as novel targets for controlling adipose tissue inflammation. Therefore, the relationship between adipokines and miRNA is worth studying. MiR-335 is an adipogenesis-related miRNA and implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 36 publications
1
62
1
Order By: Relevance
“…Stouthard et al reported that increased glucose transport was observed in 3T3-L1 adipocytes following IL-6 treatment [29] and that IL-6 may lead to mitochondria dysfunction by inducing oxidative stress [30]. In addition, IL-6 has been shown to regulate adipocyte-related microRNA expression, such as the expression of miR-335 [16]. In this study, we explored the most likely effect of IL-6 on miR-378 during adipocyte differentiation, and we observed that IL-6 induced miR-378 expression in human mature adipocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stouthard et al reported that increased glucose transport was observed in 3T3-L1 adipocytes following IL-6 treatment [29] and that IL-6 may lead to mitochondria dysfunction by inducing oxidative stress [30]. In addition, IL-6 has been shown to regulate adipocyte-related microRNA expression, such as the expression of miR-335 [16]. In this study, we explored the most likely effect of IL-6 on miR-378 during adipocyte differentiation, and we observed that IL-6 induced miR-378 expression in human mature adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, samples were incubated at 95 °C for 10 min for an initial denaturation, followed by 40 PCR cycles of incubation at 95 °C for 15 s and then 60 °C for 1 min. miRNA expression was normalized to snRNA U6 and miR-103 [16]. Primer identification numbers are 000567 for hsamiR- 378, 000439 for miR-103, and 001973 for snRU6 (ABI, Foster City, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of miRNAs in inflammatory response in many diseases has been reviewed (49). Among miRNAs associated with inflammation, miR-155 is overexpressed in adipose tissue from obese patients (32), and miR-335 expression is stimulated by leptin, resistin, TNF-␣, and IL-6 in human adipocytes (91). Investigations of miR-132 expression in human primary preadipocytes and in differentiated adipocytes established a relationship between overexpression of miR-132 and induction of nuclear factorkappa B translocation, acetylation of p65, and production of IL-8 and monocyte chemoattractant protein-1 (MCP-1).…”
Section: Mirna-mediated Regulation Of Insulin Sensitivity In Adipose mentioning
confidence: 99%
“…Regulation of the transcription of miR-335 by these adipokines is independent of the native gene (the gene MEST). Accordingly, the occurrence of complications of obesity caused by the function of miR-335 is dependent on his own mechanisms of transcription regulated by the presence of the adipokines (Zhu et al, 2014). Bielicki, et al (2014) investigated the relationship between polymorphisms of selected genes possibly associated with coronary heart disease with a prevalence of obstructive sleep apnea (OSA).…”
Section: Adiponectin -The Adipokine Of Special Rolementioning
confidence: 99%